Trombobectomia com anel de Vollmar e utilização do cateter de Fogarty no tratamento da trombose jugular experimental em equinos - Pizzigatti, Dietrich [UNESP] (2015)
The jugular thrombosis in horses commonly occurs in iatrogenic situations secondary to endotoxemia, and disseminated intravascular coagulation, which may lead to death. Prophylactic treatment with antithrombotic agents has reduced the severity of the cases. However, in situations where there chronic cases, with intense adhesion of thrombus to the vessel, drug therapy may be unsatisfactory and surgical intervention is required. The objective of this study is to evaluate the applicability of thrombectomy with Vollmar ring and watch the action of the passage of the Fogarty catheter through adhered thrombi. 10 healthy horses were used and divided into two groups of five animals each, treated with Vollmar ring and Fogarty catheter (GVF) and only with the Fogarty catheter (GF), after 13 days from unilateral right jugular vein thrombosis induction. During twenty-eight days (D0-28), the animals were evaluated at specific times, as the physical parameters, thermography, laboratory, ultrasound and phlebography, comprising four evaluation periods: the pre-induction of thrombophlebitis time (MPIT); Induction period of thrombophlebitis (MIT), which is 72 hours duration; thrombophlebitis the period (MT), where the animals was evaluated for ten days; and evaluated in divided groups (GF x GVF) after application of thrombosis correction techniques, the postoperative period (MPT). Quantitative data were compared following mean and standard deviation. Laboratory tests were evaluated by comparing the treatments by analysis of variance ANOVA. Already sonographic data were evaluated in two phases, the comparison point and segment and treatments. In both analyzes, significance values below p <0.05 were submitted to Tukey test. By analyzing the data, we observed laboratory findings and similar physiological parameters between the groups, no escape from physiological patterns or present differences than expected by the use of ...